Childbirth or termination of pregnancy: does paid employment matter? A population study of women in reproductive age in Norway - Eskild, Anne (Acta Obstet Gynecol Scand, 2016)
INTRODUCTION: We studied whether female paid employment is associated with pregnancy outcome; childbirth or pregnancy termination. MATERIAL AND METHODS: All women in Norway, 16–54 years of age, during the years 2007–10 were included. Data sources were; the Norwegian Central Person Registry, the Medical Birth Registry of Norway, and the Registry of Pregnancy Termination. We compared the proportion without paid employment among all women, women who gave birth, and among women who requested termination of pregnancy. Thereafter, and among pregnant women, we estimated the odds ratio for pregnancy termination request for women without paid employment by applying logistic regression analyses, using women with paid employment as reference. RESULTS: Among all women 16–54 years of age, 23.5% were without paid employment. Among women who gave birth, 15.8% were without paid employment, whereas this proportion was 46.4% among women who requested pregnancy termination (p < 0.05). Among the 307 512 women who were pregnant, 60 734 (19.4%) requested pregnancy termination. The odds ratio for pregnancy termination request was 3.18 (95% CI 3.11–3.25) for women without paid employment. Adjustments were made for age, number of children, and region of residence in Norway. CONCLUSION: Being without paid employment was more common among women in the general population and among women requesting pregnancy termination than among women who gave birth. Hence, women seem to have children when they are in paid employment. The role of women's paid employment for reproductive choices should be further investigated.